The relationships between high school mathematics and pre-calculus performance in university / Wan Noor Hayatie Wan Abdul Aziz ... [et al.] - Wan Abdul Aziz, Wan Noor Hayatie; Abdul Rahman, Anisah; Md Said, Junaida; Shaffie, Siti Salihah (Universiti Teknologi MARA, Perak, 2019)
Pre-Calculus is an introductory calculus course compulsory for most program under science and technology cluster in UiTM. In UiTM Perak Branch, Tapah Campus alone, 4 programs are required to undertaken Pre-Calculus during their first semester. Even so, previous exam results showed students' achievement in the Pre-Calculus course is still moderate and unsatisfactory. This study believed that students who take Additional Mathematics subject during secondary school can understand and perform better in Pre-Calculus compare to other students who were not. Therefore, this study aims to examine the relationship between Mathematics subject’s achievement during secondary school with Pre-Calculus performance in UiTM. Descriptive analysis and Pearson correlation was used to identify the relationship among three courses which are Mathematics, Additional Mathematics and Pre-Calculus using SPSS. The findings showed that there were significant correlations between the three courses; mathematics at SPM level with Pre-Calculus (correlation, r = 0.416, p-value = 0.003 <0.05), Additional Mathematics and Pre-Calculus (r = 0.385, p = 0.007 <0.05) and mathematics with Additional Mathematics (r = 0.591, p = 0.000 <0.05). Overall, the finding depicted the achievement of mathematics will help student’s performance in Pre-Calculus.